Exploration of Ethnomathematics Concepts in Geometry within Papuan Cultural Heritage Using GeoGebra - Irawati Irawati; Timbul Yuwono; Rosita Dwi Ferdiani; Defti Maulindra (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2026)
This study aims to explore the geometric concepts contained in Papuan cultural heritage and integrate them into mathematics learning. The main focus of this study is on three Papuan cultural heritages, namely the Honai traditional house, the Papuan Crown, and the Tifa. These three cultural artifacts not only have deep cultural value but also contain geometric principles that are relevant to mathematics learning. The method used in this study is qualitative research with an ethnographic approach, which involves direct observation and documentation. The data obtained is then analyzed using GeoGebra software to visualize and analyze the geometric shapes in the cultural heritage. The results of the study show that each Papuan cultural heritage contains geometric principles that can be used as examples in mathematics learning, as well as contributing to the development of ethnomathematics learning. The Honai Traditional House, with its circular base, tubular body, and conical roof, reflects the application of stable and efficient geometry. The Papuan crown, with a semicircular base and decorations that contain the principles of rotation, reflection, and dilation, demonstrates the application of symmetrical and harmonious geometry. The Tifa, which is cylindrical or tubular in shape with geometric elements in the form of circles at the top and decorations in the form of isosceles triangles, equilateral triangles, and kites, also reflects the application of significant geometric principles. This study recommends further development related to the application of GeoGebra in ethnomathematics learning and the development of ethnomathematics-based e-LKPD that highlights the cultural heritage of Papua. Thus, it is hoped that mathematics learning can become more contextual and relevant to local culture, as well as provide a more interactive and meaningful learning experience for students. Keywords: Ethnomathematics, GeoGebra, Geometry, Papuan Cultural Heritage.